Women with a BMI ≥ 30 kg/m² and their experience of maternity care: A meta ethnographic synthesis. (October 2017) - Jones, Catriona; Jomeen, Julie
Abstract: Objective: this paper is a report of a systematic review and meta-ethnography of the experiences of women with body mass index (BMI) ≥ 30 kg/m² and their experience of maternity care. Method: systematic review methods identified 12 qualitative studies about women's experiences of maternity care when their BMI ≥ 30 kg/m². Findings from the identified studies were synthesised into themes, using metaethnography. Synthesis and findings: the meta-ethnography produced four key concepts; Initial encounters, Negotiating risk, Missing out and The positive intervention, which represent the experiences of maternity care for women with BMI ≥ 30 kg/m² Key conclusion: many women with BMI ≥ 30 kg/m² appear to be dissatisfied with the approaches taken to discuss weight status during maternity encounters. When weight is not addressed during these encounters women appear to be equally dissatisfied. The absence of open and honest discussions about weight, the feeling of being denied of a normal experience, and an over emphasis on the risks imposed upon pregnancy and childbirth by obesity, leave women feeling dissatisfied and disenfranchised. Sensitive care and practical advice about diet and exercise can help women move towards feeling more in control of their weight management Highlights: Many pregnant women who are categorised as obese appear to be dissatisfied with the way in which their weight status is addressed (or not) when engaging with healthcare. The absence of open and honest discussions about weight leaves women feeling dissatisfied. Balanced care and support helps women feel more in control of weight management.